Ricerche sull'unità dauna: biostratigrafia e sedimentologia della successione di Monte Sidone nell'appennino dauno (Italia meridionale) - Russo, B.; Senatore, M. R. (1989)
The Daunia Unit according to Senatore (1988) consists of three different formations: Calcarenites, marls, and clays of Monte Sidone formation (Senatore, 1988), Faeto Flysch formation (Crostella & Vezzani, 1964) and Clayey Marls of Toppo Capuana formation (Crostella & Vezzani, 1964). The Daunia Unit sequence is characterized by turbiditic calcareous-clastic, marly and clayey sediments. The Faeto Flysch formation comprises almost exclusively calcareous — marly sediments. According to the planktonic foraminifera associations, the Daunia Unit has an age comprised between the upper Aquitanian and the midd1eupper Tortonian. The lithostratigraphical and sedimentological characteristics of the Daunia Unit allow us to hypothesize that il deposited in a basin on the edge of a neritic carbonatic platform (Apulia Platform). This basin did not receive siliceous-clastic sediments during the early Langhian-early Tortonian, At the same time siliceous clastic sequences, known as Irpinian Units, deposited in the western and southern basin areas.